2022
DOI: 10.3390/ijms23073513
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CFTR Modulators on Airway Infection in Cystic Fibrosis

Abstract: The advent of Cystic fibrosis transmembrane receptor (CFTR) modulators in 2012 was a critical event in the history of cystic fibrosis (CF) treatment. Unlike traditional therapies that target downstream effects of CFTR dysfunction, CFTR modulators aim to correct the underlying defect at the protein level. These genotype-specific therapies are now available for an increasing number of CF patients, transforming the way we view the condition from a life-limiting disease to one that can be effectively managed. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 138 publications
0
16
0
3
Order By: Relevance
“…Some studies reported that the CFTR modulators may reduce bacterial load, microbial burden and restore innate immune responses and bacterial diversity similar to people without CF, thereby yielding an airway microbiome which reduces the incidence of acute airway infection and the rate of lung decline [38,39]. Another study contradicts this by reporting that treatment with ivacaftor does not reduce the odds of culture positivity with common CF-related microorganisms such as S. aureus [39]. CFTR modulators have not demonstrated change in antibiotic susceptibility of microorganisms and have no impact on the control of viral infection in the CF airway epithelial cells [40][41][42].…”
Section: Cf and Microbial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that the CFTR modulators may reduce bacterial load, microbial burden and restore innate immune responses and bacterial diversity similar to people without CF, thereby yielding an airway microbiome which reduces the incidence of acute airway infection and the rate of lung decline [38,39]. Another study contradicts this by reporting that treatment with ivacaftor does not reduce the odds of culture positivity with common CF-related microorganisms such as S. aureus [39]. CFTR modulators have not demonstrated change in antibiotic susceptibility of microorganisms and have no impact on the control of viral infection in the CF airway epithelial cells [40][41][42].…”
Section: Cf and Microbial Infectionsmentioning
confidence: 99%
“…However, the literature reveals contrasting reports on this topic. Some studies reported that the CFTR modulators may reduce bacterial load, microbial burden and restore innate immune responses and bacterial diversity similar to people without CF, thereby yielding an airway microbiome which reduces the incidence of acute airway infection and the rate of lung decline [ 38 , 39 ]. Another study contradicts this by reporting that treatment with ivacaftor does not reduce the odds of culture positivity with common CF-related microorganisms such as S. aureus [ 39 ].…”
Section: Cf and Microbial Infectionsmentioning
confidence: 99%
“…Weight gain (BMI increase) [27,33]. Current scientific evidence suggests that modulators of CFTR protein function are unable to eliminate airway colonization by pathogens in patients with advanced lung disease [37,38]. This seems to be an important observation considering that patients often have symptoms of infection and chronic inflammation of the airways, and most people with cystic fibrosis die of advanced lung disease [38].…”
Section: Ivacaftor + Tezacaftormentioning
confidence: 99%
“…Current scientific evidence suggests that modulators of CFTR protein function are unable to eliminate airway colonization by pathogens in patients with advanced lung disease [37,38]. This seems to be an important observation considering that patients often have symptoms of infection and chronic inflammation of the airways, and most people with cystic fibrosis die of advanced lung disease [38]. For this reason, the prevention of infections and the use of antimicrobial agents should be a necessary complement to the therapy using modulators of CFTR protein function.…”
Section: Ivacaftor + Tezacaftormentioning
confidence: 99%
“…In part, this may relate to heterogeneity of deposition within partially obstructed airways, giving rise to subtherapeutic drug concentrations. Few new treatments are being developed for chronic P. aeruginosa , and the growing adult population means this unmet need will persist into the era of novel modulator drugs targeting the underlying cellular defect in CF ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%